A Novel Energy Storage Allocation Planning Method for Microgrid - (:unkn) unknown (My University, 2016)
This paper proposes a novel energy storage system planning method with real time control. Sensitivity analysis is used to linearize the real power change in each certain generator brought by wind and ESS power change in system. Particle Swarm Optimization (PSO) is modified to include the real power change percentage as a constraint, and used to determine optimum ESS size and location. After extensive tests, it shows that this method can determine the optimum sizes and locations for ESS which can effectively keep the disturbance on generators in a system to the minimum while maintaining an acceptable system voltage profile after a sudden wind power drop.
Keywords: ESS; Planning; PSO; Sensitivity Analysis